Note-Taking Strategy for EFL Students Listening Comprehension of Narrative Text - Nurani, Salsabila Gita; Nurazizah, Asti Siti; Damayanti, Luh Sri; Dewantara, Kadek Andre Karisma; Armawan, Ketut (Journal of English Language and Education, 2025)
This study aims to prove whether note-taking strategy has significant effect to help EFL senior high school students to get better score of listening comprehension of narrative text. This study used pre-experimental design to 14 second-year students of SMA Al-Fattah Singosari. The participants were given pretest, treatment, and posttest. The pretest was the condition of the students when listening to narrative audio without taking notes whereas the posttest was the condition of the students when listening to narrative audio with taking notes. Then the treatment was students had to write the important points of narrative text such as characters, characteristics, conflict, and ending. The results showed that the students achieved better score of listening comprehension of narrative text when they were instructed to take notes. It means note-taking strategy can effectively help the students to get better score of listening comprehension of narrative text.